Biocombustíveis e mudanças climáticas: a política nacional de biocombustíveis (renovabio) e sua contribuição para o atendimento dos compromissos brasileiros no acordo de paris (cop21) - Macedo, Luiz César Machado de (2021)
This thesis discusses the institutional design and implementation of the National Biofuels Policy (RenovaBio), from its foundations, principles, guidelines, tools and actions that aim to meet the Brazilian international commitment formalized in its Nationally Determined Contribution (NDC).